Automatic Baby Stroller - Rashed, Ola (2021)
Technology is being enhanced around us every day, every one of us is very dependent on technology that we can't live or do without. Starting from computers to keeping fit, every step of the way we need technology. Innovation is a need that we can't escape from. It has a very important job in many parts of our lives. As it answers the vast majority of human issues. Over the hundreds of years, innovation is developing the significance of utilization in whatever structure it is. As a result, technology is generally coordinated for ease and comfort throughout everyday life. The Automatic Baby Stroller will change the parents' experience and take it to a different level. This baby stroller will feature security, app, temperature-controlled storage, and sensors. The installed sensors will be distance controlled sensor that will detect the place of the user via the mobile phone and through an app (Bluetooth) the baby stroller is supposed to move synchronously with the user's movement. Also, there will be a noise detector i.e., when the baby cries, there will a notification sent to the user's app that the baby is crying if the user was away. Moreover, there will be a sensor that will move the stroller back and forth with controlled distance through the application to calm the baby or put it to sleep. A USB flash drive will take place and some installed speakers for music. Furthermore, there will be a camera in the stroller for security that the user can monitor the baby if away through the app. Also, there will be a space for storage, baby needs along with a temperature controller for the milk; there will also be a wheel lock to secure the stroller and if it was moved intentionally or lifted, there will be alarm noise. This project serves paralyzed, or parents with prostheses, multiple children parents. Also, it will limit the kidnappings happening with the stroller.